2010
DOI: 10.2514/1.46815
|View full text |Cite
|
Sign up to set email alerts
|

Air-Combat Strategy Using Approximate Dynamic Programming

Abstract: Unmanned Aircraft Systems (UAS) have the potential to perform many of the dangerous missions currently flown by manned aircraft. Yet, the complexity of some tasks, such as air combat, have precluded UAS from successfully carrying out these missions autonomously. This paper presents a formulation of a level flight, fixed velocity, one-on-one air combat maneuvering problem and an approximate dynamic programming (ADP) approach for computing an efficient approximation of the optimal policy. In the version of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(80 citation statements)
references
References 17 publications
0
80
0
Order By: Relevance
“…Here control strategies are usually generated for one side while assuming some model that predicts the actions of the opposing side. One approach uses nonlinear model-predictive control to generate control inputs for an unmanned aerial vehicle [12], while another uses approximate dynamic programming for a similar application [13]. In both cases, adversary actions are predicted based upon expected opponent strategies, with feedback and re-planning used to adjust for deviations from the predicted actions at run-time.…”
Section: Introductionmentioning
confidence: 99%
“…Here control strategies are usually generated for one side while assuming some model that predicts the actions of the opposing side. One approach uses nonlinear model-predictive control to generate control inputs for an unmanned aerial vehicle [12], while another uses approximate dynamic programming for a similar application [13]. In both cases, adversary actions are predicted based upon expected opponent strategies, with feedback and re-planning used to adjust for deviations from the predicted actions at run-time.…”
Section: Introductionmentioning
confidence: 99%
“…In complex pursuit-evasion games where players may change roles over time, a nonlinear model-predictive control [8] approach has been investigated. Approximate dynamic programming [9] has also been used to analyze reach-avoid games.…”
Section: Introductionmentioning
confidence: 99%
“…Blue (10) Here, K H is also a constant and B Critical means the lower bound. These penalty terms are applied to the scoring function exponentially right after the relative orientation of two aircrafts is evaluated.…”
Section: Redmentioning
confidence: 99%
“…To overcome the complexity of calculation and difficulty in real-time simulation, variations of dynamic programming have been suggested by researchers. McGrew et al [9][10] have suggested an approximate dynamic programming method to find the air combat strategy. Approximate dynamic programming is different from classical dynamic programming in that it formulates a continuous function to approximately represent the future reward.…”
Section: Introductionmentioning
confidence: 99%